Functional Genomics of the Aeromonas salmonicida Lipopolysaccharide O-Antigen and A-Layer from Typical and Atypical Strains - Susana Merino; Elena de Mendoza; Rocío Canals; Juan M. Tomás (Marine Drugs, 2015)
The A. salmonicida A450 LPS O-antigen, encoded by the wbsalmo gene cluster, is exported through an ABC-2 transporter-dependent pathway. It represents the first example of an O-antigen LPS polysaccharide with three different monosaccharides in their repeating unit assembled by this pathway. Until now, only repeating units with one or two different monosaccharides have been described. Functional genomic analysis of this wbsalmo region is mostly in agreement with the LPS O-antigen structure of acetylated l-rhamnose (Rha), d-glucose (Glc), and 2-amino-2-deoxy-d-mannose (ManN). Between genes of the wbsalmo we found the genes responsible for the biosynthesis and assembly of the S-layer (named A-layer in these strains). Through comparative genomic analysis and in-frame deletions of some of the genes, we concluded that all the A. salmonicida typical and atypical strains, other than A. salmonicida subsp. pectinolytica strains, shared the same wbsalmo and presence of A-layer. A. salmonicida subsp. pectinolytica strains lack wbsalmo and A-layer, two major virulence factors, and this could be the reason they are the only ones not found as fish pathogens.